2020
DOI: 10.3390/agronomy10121980
|View full text |Cite
|
Sign up to set email alerts
|

Fodder Yield, Quality and Growth of Chia (Salvia hispanica L.) as Affected by Sowing Density and Top-Dressing Nitrogen Fertilization

Abstract: Chia (Salvia hispanica L.) seeds are considered a superfood, but research on vegetative biomass uses is scarce. We conducted a two-year trial under the hypothesis that short-day flowering black chia would provide quality forage at high latitudes and tested sowing density (D1 = 125, D2 = 25, D3 = 8 and D4 = 4 plants m−2) and top-dressing N fertilization (N = 0, N = 20 kg ha−1) at three stages (EV = early vegetative, LV = late vegetative and EF = early flowering). Forage yield reached 9.0 and 5.64 t ha-1 of tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
(80 reference statements)
1
1
0
Order By: Relevance
“…77°31′W), compared well with other reports and were impressive. Crude protein in Chia produced in Virginia varied from 17 to 21 percent and compared well with literature values of alfalfa hay (19 percent, Meyer et al, 2010), perennial peanut (14 percent, Meyer et al, 2010), soybean forage (19.8 percent, Lundry et al, 2008), and those of Chia reported to vary from 8 to 18 percent by Rossi et al (2020) from Italy.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…77°31′W), compared well with other reports and were impressive. Crude protein in Chia produced in Virginia varied from 17 to 21 percent and compared well with literature values of alfalfa hay (19 percent, Meyer et al, 2010), perennial peanut (14 percent, Meyer et al, 2010), soybean forage (19.8 percent, Lundry et al, 2008), and those of Chia reported to vary from 8 to 18 percent by Rossi et al (2020) from Italy.…”
Section: Resultssupporting
confidence: 76%
“…These data suggest that Chia could be successfully used as an alternative forage crop. Rossi et al (2020) reported that Chia total plant yield varied from 5.64 to 9.0 t/ha during 2013 and 2014 when grown in Italy and crude protein varied from 18 to 8 percent from early vegetative and early flowering stages, respectively. These authors suggested that Chia has potential as a forage crop.…”
Section: Resultsmentioning
confidence: 99%